BLOOD PARAMETERS, NONSPECIFIC RESISTANCE, AND PRODUCTIVITY OF FINE-WOOL SHEEP OF DIFFERENT GENOTYPES - E. A. Lakota; O. A. Vorontsova; I. A. Polnikov; Yu. I. Galtsev (Вавиловский журнал генетики и селекции)
Long-term studies carried out in the south-east of Saratov Oblast prove that the introductive crossing of the Stavropol wool breed to rams of the wool–meat double purpose increases the offspring live weight, wool yield, and meat productivity, as well as their adaptive capacity and preservation. The experimental data have been obtained in research farms of Saratov Oblast on the base of breeding farms “Krasnyi Partizan” and “Novouzensk”. The breeding involves wool–meat breeds: Caucasian and Transbaikalian. The results show that the mating of rock wool Stavropol sheep to Caucasian and Transbaikalian rams increases body weight and wool clip. It also strengthens the physique and the viability of the young. Along with these indications for selection, the level of natural resistance and adaptive potential of animals are of great importance. Assays of biochemical and hematological indices, humoral factors have shown that the hybrids, as compared to purebred peers, are more productive and have a higher adaptive capacity, which is a significant economic indicator in the modern sheep industry.